Stimulation role of pollen grains in the initial development of Botrytis cinerea: The importance of host compatibility, cultivation status and pollen size. Issue 11 (17th October 2022) - Kocsis, Ivett; Petróczy, Marietta; Takács, Kolos Zoltán; Markó, Gábor
Abstract: Plant pollens and fungal spores are massively produced in natural habitats and large‐scaled agricultural areas, and the airborne transported biomass can be accumulated on relatively large crop surfaces. A pollen grain contains a specific chemical composition in quantity and quality, highly varied among plant species. So, the accumulated pollens could provide a species‐specific nutrient supply for the initial fungal development in a pollen trap. Thus, this could increase the variation of the pathogen infection risk in certain plants due to selection mechanisms such as host–pathogen coevolution, crop breeding or pollination type. However, the role of the pollen‐stimulated spore germination and the species‐specific differences in the pollen‐spore interferences is still less understood. Therefore, we performed a multispecies experimental comparison (including 20 plant species) to test the role of the taxon‐specific attributes (i.e. host–pathogen compatibility, cultivation, pollination type and pollen size) in the dose and temporal response of the spore germination in Botrytis cinerea . We found a strong pollen‐stimulating effect on spore germination; however, the triggering effect highly varied among plant species and differed between specific functional categories across temporal and concentration gradients. Specifically, the B. cinerea hosts, the non‐cultivated plants and species with larger pollen size, increased the spore germination's stimulation effects, but not the pollination type. The systematic taxonomic and functional differences might reflect indirectly the diversity of the pollens' chemical profile (i.e. composition matrix or specific trigger molecules) which different selection mechanisms might shape. In the crop–pathogen interactions, the pollen‐stimulation effect could play an essential role in early fungal development.